Surgical management of single-level thoracolumbar vertebral body segmentation and formation failure causing progressive thoracolumbar myelopathy in three adult large-breed dogs - Couto, Francisca; Tabanez, Joana; Rose, Jeremy; Driver, Colin (Frontiers in Veterinary Science, 2025)
ObjectiveThis study aimed to evaluate the medium-term outcome following spinal cord decompression and instrumented fixation of single-level congenital thoracolumbar vertebral malformations, characterized by combined failures of segmentation and formation, causing thoracolumbar myelopathy in three large-breed dogs.Study designThis was a retrospective clinical study.AnimalsThe animals involved in the study were three large-breed dogs.MethodsElectronic patient records were retrospectively reviewed for adult large-breed dogs (>1 year) (>25 kg) with thoracolumbar myelopathy and a radiologic diagnosis of spinal cord compression associated with thoracolumbar vertebral malformation. The examination, diagnostic imaging, surgical management, and outcomes are described. The medium-term outcome was determined based on the neurological examination and follow-up imaging studies conducted up to 12 months post-operation.ResultsThree large-breed dogs were identified, presenting with progressive, non-painful T3–L3 spinal cord segment disease. Diagnosis was made using MRI and CT, which revealed single-level complex congenital vertebral malformation with combined failures of segmentation and formation in the T8–L1 region. Surgical management consisted of ventral cord decompression by bilateral mini-hemilaminectomy and partial corpectomy and vertebral fixation. Temporary postoperative neurological deterioration was observed in two cases. Follow-up was conducted at 6 weeks (examination) and 3 (examination), 6, and 12 months (examination and CT) postoperatively, and improved neurological function was confirmed, with all cases being ambulatory with persistent, mild paraparesis.ConclusionThis retrospective study demonstrates the successful medium-term outcome following surgical management of complex thoracolumbar vertebral malformations in large-breed dogs.